2022
DOI: 10.3389/fphar.2022.939090
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti-Cancer Therapy: CRISPR/Cas9 Gene Editing

Abstract: Cancer becomes one of the main causes of human deaths in the world due to the high incidence and mortality rate and produces serious economic burdens. With more and more attention is paid on cancer, its therapies are getting more of a concern. Previous research has shown that the occurrence, progression, and treatment prognosis of malignant tumors are closely related to genetic and gene mutation. CRISPR/Cas9 has emerged as a powerful method for making changes to the genome, which has extensively been applied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…However, the off-target effect and delivery with minimal systemic toxicity limit clinical applications. 52 With this knowledge, we tried to develop a targeted and safe gene editing of HPV16-associated tumors using CRISPR/Cas9 method in C57BL/6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the off-target effect and delivery with minimal systemic toxicity limit clinical applications. 52 With this knowledge, we tried to develop a targeted and safe gene editing of HPV16-associated tumors using CRISPR/Cas9 method in C57BL/6…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas technique brings great promise for inhibiting migration and invasion. However, the off‐target effect and delivery with minimal systemic toxicity limit clinical applications 52 . With this knowledge, we tried to develop a targeted and safe gene editing of HPV16‐associated tumors using CRISPR/Cas9 method in C57BL/6 mice, and explored the potential of using CPPs in systemic delivery of CRISPR/Cas9‐mediated therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CRISPR technology has been extended to the clinic ( 143 145 ) ( Figure 2D ). Initial proof-of-concept clinical trials in advanced esophageal (NCT03081715), metastatic non-small cell lung ( 146 ), and advanced, refractory cancer (NCT03399448) ( 147 ) have demonstrated CRISPR-Cas9 editing of autologous CAR T cells prior to adoptive transfer to be safe and feasible.…”
Section: Discussionmentioning
confidence: 99%
“…[34,49] Although some previous studies have demonstrated systemic delivery of the CRISPR/Cas9 system to tumors based on conventional nano-formulations, the efficiency of delivering the RNPs, in general, has been extremely low. [50,51] In the clinic, intratumoral delivery has been a widely used route for adenovirus-based therapy. [52] Here, we show the efficacy of the ComBiNE platform through an intratumoral route, which can bring a substantial impact on cancer treatment in the clinic.…”
Section: In Vivo Efficacy Of Combine For Combinatorial Therapy In a B...mentioning
confidence: 99%